2007
DOI: 10.1051/agro:2007020
|View full text |Cite
|
Sign up to set email alerts
|

Microbial impact of the pesticide chlorpyrifos on Swedish and Italian biobeds

Abstract: -Biobeds provide a simple and cheap solution to reducing point-source contamination by pesticides from farm activities. In its original design, the Swedish biobed is a clay-lined pit in the ground filled with a biomixture of topsoil, peat and straw and covered with a grass layer. The straw stimulates the growth of lignin-degrading fungi and the formation and activity of ligninolytic enzymes which can degrade many different pesticides. Here we compared the behaviour of the chlorpyrifos pesticide in two biobeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 18 publications
0
21
0
3
Order By: Relevance
“…Though the null effect of chlorpyrifos on soil microbial biomass had been reported (Adesodun et al 2005), impacts of chlorpyrifos on soil microbial characteristics including microbial biomass, microbial populations, microbial respiration, enzymatic activities, and mineral cycling have been frequently studied. Findings indicated statistically (2000) Environ Chem Lett significant reduction in soil microbial biomass (Vischetti et al 2007), and soil enzyme activities (Singh et al 2003a) resulted from repeated application of chlorpyrifos and accumulation of 3,5,6-trichloro-2-pyridinol. There are contradictory evidences on changes in microbial population due to chlorpyrifos application.…”
Section: Toxicity Concerns Toxicity On Microorganismsmentioning
confidence: 99%
“…Though the null effect of chlorpyrifos on soil microbial biomass had been reported (Adesodun et al 2005), impacts of chlorpyrifos on soil microbial characteristics including microbial biomass, microbial populations, microbial respiration, enzymatic activities, and mineral cycling have been frequently studied. Findings indicated statistically (2000) Environ Chem Lett significant reduction in soil microbial biomass (Vischetti et al 2007), and soil enzyme activities (Singh et al 2003a) resulted from repeated application of chlorpyrifos and accumulation of 3,5,6-trichloro-2-pyridinol. There are contradictory evidences on changes in microbial population due to chlorpyrifos application.…”
Section: Toxicity Concerns Toxicity On Microorganismsmentioning
confidence: 99%
“…It is effective against a broad spectrum of agricultural and household pests. The behaviors of chlorpyrifos in soil were studied intensely due to its long persistence in soil environments and harmful impacts upon organisms (e.g., Racke et al, 1998;Yucel et al, 1999;Singh et al, 2003;Ngan et al, 2005;Fang et al, 2006;Vischetti et al, 2007;Fang et al, 2008;Vejares et al, 2010). Earthworms comprise the largest proportion of the biomass of the soil fauna and contribute to the process of cycling of nutrients in terrestrial ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with northern Europe, little is known about the implementation of biobeds in southern Europe, where agricultural practices and climatic conditions differ greatly. Over the past 5 years, a series of studies in Italy has shown that a biomixture consisting of various composted materials instead of peat, and macerated vine branches instead of straw, has high degradation capacity,11–13 and it has been utilised in a prototype biobed system constructed in northern Italy 14. However, no other studies are available regarding biobeds in the Mediterranean region.…”
Section: Introductionmentioning
confidence: 99%